Reformasi Birokrasi Melalui E-Government Dalam Upaya Peningkatan Kualitas Pelayanan Permata Di Kantor Pertanahan Kota Semarang (Forum Ilmu Sosial, 2019)
The case in the Land Office Semarang included: the service is slow, cumbersome, expensive; so while the energy and infrastructure was minimal.This study aimed to describe bureaucratic reforms undertaken to improve the quality of service in the land sector, and the role of e-Government through Permata Program (Self Registration of the Land Deed), to be examined Community Satisfaction Index (CSI) through that.This research was qualitative-quantitative, with the case study method. The data obtained through interviews, observation, and literature study. The conclusions from the study were the reform of the bureaucracy in the public service system was implemented in order to realize good governance through the implementation of e-Government with that service innovation; Land Deed Officer as user Permata was satisfied with the services of the agency. The result of the calculation CSI is 75.08, the value and quality of service is B, and the performance of the Public Service Unit Permata is good. The title as the Office of Type "A" among Regional Offices of Central Java in 2014 and the appreciation of the "Top 99 Innovations Online Servicesâ€ in 2015 are proofs to its performance achievement.